China's Co-Operation with Central Asian Countries on Cyber Security - Mura, Sarybayev; Yeleukhan, Kaliyeva; Duman, Zhekenov; Parkhatzhan, Islambek (Journal of Posthumanism, 2025)
The issue of cyber security is becoming more and more important today, so this factor must be taken into account by all governments, because threats in the field of information technology are no less important than threats in any other sphere of state activity. So, cybersecurity is the state or process of protecting and recovering computer systems, networks, devices and programmes from any type of cyberattack. Cyberattacks pose an increasingly sophisticated and growing threat to sensitive user data worldwide as attackers use new techniques based on social engineering and artificial intelligence to circumvent traditional data security controls. It is worth noting that the modern world is increasingly reliant on computer technology, and this reliance will only increase over time. In particular, this is fuelled by a generation of new technologies that will access our connected devices via Bluetooth and Wi-Fi, making it easier for attackers to commit illegal acts.